Examination of a partial dietary self‐monitoring approach for behavioral weight management. (26th April 2020) - Tate, Deborah F.; Quesnel, Danika A.; Lutes, Lesley; Hatley, Karen E.; Nezami, Brooke T.; Wojtanowski, Alexis C.; Pinto, Angela M.; Power, Julianne; Diamond, Molly; Polzien, Kristen; Foster, Gary
Summary: Introduction: Dietary self‐monitoring in behavioral weight loss programmes traditionally involves keeping track of all foods and beverages to achieve a calorie deficit. While effective, adherence declines over time. WW™ (formerly Weight Watchers), a widely available commercial weight management programme, sought to pilot an approach that permitted participants to consume over 200 foods without monitoring them. Methods: The current study used a pre‐post evaluation design with anthropometric, psychosocial and physical health assessments at baseline, 3 and 6 months. Results: Participants ( N = 152) were, on average, 48.4 (±12.3) years old, with body mass index (BMI) of 32.8 (±4.8) m/kg 2 and 94% female. Mean weight loss was 6.97 + 5.55 kg or 7.9 ± 6.1% of initial body weight ( p s < .0001) at 6 months. One third (32.6%) of the sample lost 10% or more of initial body weight. Significant improvements in hunger, cravings, happiness, sleep, quality of life, aerobic stamina, flexibility and blood pressure were observed. Attendance at group meetings, as well as decreases in hunger, and fast food cravings from baseline to 3 months were associated with achieving 10% weight loss at 6 months ( p < .01). Conclusions: Using an approach that does not require self‐monitoring of all foods and beverages produced significant weight losses and other physical and psychosocial improvements.